Evolution of retinal changes measured by optical coherence tomography in the assessment of hydroxychloroquine ocular safety in patients with systemic lupus erythematosus. (April 2019) - Martín-Iglesias, D; Artaraz, J; Fonollosa, A; Ugarte, A; Arteagabeitia, A; Ruiz-Irastorza, G
Objective: The objective of this report is to analyse retinal changes over a five-year period, assessed by spectral domain-optical coherence tomography (SD-OCT), in patients from the Lupus-Cruces cohort treated with hydroxychloroquine (HCQ). Methods: SD-OCT screening was performed annually between 2012 and 2017. Average macular thickness (AMT), ganglion cell layer thickness (GCLT) and qualitative data of retinal pigment epithelium (RPE) and external retina (ExtR) were collected prospectively. We compared data from 2012 (first) and 2017 (second) SD-OCT. Results: We studied 110 patients and 195 eyes. No cases of HCQ toxicity were detected. At the time of the second SD-OCT, 99% patients had taken a daily dose of HCQ ≤5 mg/kg/day. The median time on HCQ was 133 months. The mean AMT and GCLT were significantly lower in both eyes at the second SD-OCT; however, all the differences were clinically insignificant at less than 1%. Qualitative analysis of RPE and ExtR showed no significant changes. Similar results were found among patients with risk factors for retinopathy. The comparison of patients with and without risk factors showed no differences. Conclusions: This study shows clinically irrelevant retinal changes in an SLE cohort on HCQ treatment over a five-year follow-up. Our findings support the safety of long-term HCQ at doses ≤5 mg/kg/day.